2018
DOI: 10.1002/csr.1631
|View full text |Cite
|
Sign up to set email alerts
|

Does it pay to be sustainable? Looking inside the black box of the relationship between sustainability performance and financial performance

Abstract: The last three decades have witnessed a huge amount of research exploring the linkage between companies' sustainability performance (SP), sustainability disclosure and financial performance (FP). Researchers have applied various methods and techniques to investigate this relationship, yet the results remain equivocal. In this article, we look inside this black box by considering various manifestations of sustainability practices and investigating their link with FP. We apply a manual content analysis technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(168 citation statements)
references
References 96 publications
6
128
0
13
Order By: Relevance
“…For the nonelectronics industries, the results revealed that board ownership has a significant positive influence on the CSR-CFP relationship and a negative relationship if it is a family business. Hussain, Rigoni, and Cavezzali (2018) have considered various manifestations of sustainability practices and investigated their link with CFP. Authors analyzed the sustainability reports of the 100 best performing U.S. firms and revealed that fragmentation in the results obtained is caused by the ways of sustainability performance measurement as the interlinks between different sustainability performance dimensions and subdimensions are weak and somewhat contradictory.…”
Section: Hou (2019) Examined the Relationship Between Csr And Cfp Inmentioning
confidence: 99%
See 1 more Smart Citation
“…For the nonelectronics industries, the results revealed that board ownership has a significant positive influence on the CSR-CFP relationship and a negative relationship if it is a family business. Hussain, Rigoni, and Cavezzali (2018) have considered various manifestations of sustainability practices and investigated their link with CFP. Authors analyzed the sustainability reports of the 100 best performing U.S. firms and revealed that fragmentation in the results obtained is caused by the ways of sustainability performance measurement as the interlinks between different sustainability performance dimensions and subdimensions are weak and somewhat contradictory.…”
Section: Hou (2019) Examined the Relationship Between Csr And Cfp Inmentioning
confidence: 99%
“…Institutional transitions affect the role of financial performance in CSR reporting CFP buffers against external pressures on CSR brought by institutional transitions Hou (2019) Relationship between CSR and CFP in Taiwan Socially responsible firms can achieve financial performance superior to those which do not pursue CSR initiatives Hussain et al (2018) Link between sustainability practices and CFP Interlinks between different sustainability performance dimensions and subdimensions are weak and somewhat contradictory to bias and fragment research results Lu et al (2018) Link between CSR and its material implications including CFP CSR programs can be detrimental to CFP in the short term but conducive to improving it in the long term Busch and Friede (2018) Relation between CSP and CFP The relation is positive regardless of whether firms focus on ecological or social aspects. Strong relation for operational, short-term CFP Marti et al…”
Section: Significant Differences Between Industrial Firms and Financimentioning
confidence: 99%
“…There is extensive research on the integration of sustainability or CSR into corporate strategic management [18], and particularly on the analysis of the links with economic value creation (including comprehensive reviews and meta-analysis [2,14,[19][20][21][22]); however, the results regarding the relationship between CSR and financial performance remain inconclusive [17,[23][24][25]. In particular, research findings support all the possible hypotheses (non-significant or neutral effects, positive effects and negative effects of CSP on CFP).…”
Section: The Csp-cfp Linkmentioning
confidence: 96%
“…Hussain, Rigoni & Cavezzali investigated the relationship between sustainability performance (SP) and financial performance (FP) of company. As a result, a model of assessing the impact of sustainability performance (SP) on financial performance (FP) was proposed, such a model allows us to assess the financial value of the stability of a company's development [11]. Peculiarities of corporate reporting with the goal of creating a positive image of the company, the advantages of financial and non-financial reporting from the point of view of planning sales volumes are presented in the works of a group of Singaporean scientists [12].…”
Section: Literature Reviewmentioning
confidence: 99%